1993
DOI: 10.1021/j100118a024
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio characterization of gaseous phosphorus oxide (P2O2)

Abstract: Ab initio electronic structure calculations demonstrate that a singlet planar cyclic isomer of P202 with D2h symmetry is more stable than all the previously characterized P202 isomers. A proper description of the electronic structure wavefunction is found to be essential to predict correctly the multiplicity of the ground state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 2 publications
4
20
0
Order By: Relevance
“…6 Proper choice of the computational approach and careful inspection of the results revealed that no P-P bond was present in either of the molecules. 5,6 Similarly, for the recently characterized 7 (P< O O >C) + molecule, no P-C cross bonding was found for either its ground singlet 1 A′ state or its first triplet 3 A′′ excited state. The phosphorus atom has been predicted to bear almost the whole charge unity of the molecule for both states, while the spin density on both carbon and phosphorus has comparable values for the triplet state.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…6 Proper choice of the computational approach and careful inspection of the results revealed that no P-P bond was present in either of the molecules. 5,6 Similarly, for the recently characterized 7 (P< O O >C) + molecule, no P-C cross bonding was found for either its ground singlet 1 A′ state or its first triplet 3 A′′ excited state. The phosphorus atom has been predicted to bear almost the whole charge unity of the molecule for both states, while the spin density on both carbon and phosphorus has comparable values for the triplet state.…”
Section: Introductionmentioning
confidence: 83%
“…[3][4][5][6] Thus, the minimun energy structure of the (PO) 2 species is found to be the singlet D 2h symmetric P< O O >P isomer, an species which has been shown to possess a large biradical character. 4,5 For the (PO) 2 + species, however, the doublet 2 B 2g state of the D 2h symmetry (P< O O >P) + isomer has been found to be the lowest energy isomer. 6 Proper choice of the computational approach and careful inspection of the results revealed that no P-P bond was present in either of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…7,18,21 Their possible diradical nature has been stressed only by few authors. Skrezenek and Harcourt 12,22 have considered S4 2+ to be a singlet diradical in an analogous manner to S2N2 and Lopez et al 23 have stated that the hypothetical square-planar molecule P2O2 should be highly diradical in nature and addressed the diradical character to phosphorus atoms.…”
Section: The Most Recent Contribution To the Discussion Of Bonding Inmentioning
confidence: 99%
“…On the other hand, Zachariah and Melius have made energetic calculations for various P−Si−H molecules . However, almost nothing has been done for the P−O−H molecules so far except for some calculations of P 2 O 2 , and P 2 H 4 …”
Section: Introductionmentioning
confidence: 99%